2018
DOI: 10.1007/s00436-018-5792-z
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell-nerve interaction in the colon of Trypanosoma cruzi-infected individuals with chagasic megacolon

Abstract: Chagas disease is an infection caused by the parasite Trypanosoma cruzi that affects millions of people worldwide and is endemic in Latin America. Megacolon is the most frequent complication of the digestive chronic form and happens due to lesions of the enteric nervous system. The neuronal lesions seem to initiate in the acute phase and persist during the chronic phase, albeit the mechanisms involved in this process are still debated. Among the cells of the immune system possibly involved in this pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…MC degranulation was found to be associated with nerve fiber network disintegration and loss of neuronal cell bodies in a coculture model between myenteric neurons and peritoneal MCs isolated from rats [146], and besides tryptase, other proinflammatory MC mediators such as IL-6 and prostaglandin 2 could induce neuronal death. The same was observed when a PAR2 agonist was used [146], corroborating what was suggested by Martins et al [34] in Chagasic megacolon.…”
Section: 7supporting
confidence: 88%
See 3 more Smart Citations
“…MC degranulation was found to be associated with nerve fiber network disintegration and loss of neuronal cell bodies in a coculture model between myenteric neurons and peritoneal MCs isolated from rats [146], and besides tryptase, other proinflammatory MC mediators such as IL-6 and prostaglandin 2 could induce neuronal death. The same was observed when a PAR2 agonist was used [146], corroborating what was suggested by Martins et al [34] in Chagasic megacolon.…”
Section: 7supporting
confidence: 88%
“…In fact, MCs play an important role in megacolon pathophysiology. Evidence shows that the concentration of these cells is increased regardless of the affected intestine layer [13,34,138,139]; the same has been observed in a murine chronic phase model [140]. The increase in chymase-IR and tryptase-IR MCs has been shown to be correlated with decreased PGP 9.5-IR neurons in Chagasic megacolon [34].…”
Section: 7mentioning
confidence: 57%
See 2 more Smart Citations
“…Substance P , a neuropeptide, has been shown to be increased in dilated portions of patients with chagasic megacolon, and this increase has been shown to be related to the induction/maintenance of intestinal inflammation and leukocyte chemotaxis, which may be related to neuronal damage [ 40 , 41 ]. In addition, proteases produced by mast cells, such as tryptase, are correlated with neuronal death in patients with chagasic megacolon, mainly by decreasing immunoreactive PAR2 neurons [ 42 ]. Our group demonstrated that type 2 bone morphogenetic proteins are correlated with neuronal destruction and with the maintenance of the intestinal proinflammatory profile in an acute-phase experimental model infected with the Y strain [ 10 ].…”
Section: Discussionmentioning
confidence: 99%